Effectiveness of alcohol septal ablation for hypertrophic obstructive cardiomyopathy in patients with late gadolinium enhancement on cardiac magnetic resonance. (15th November 2020) - Polaková, Eva; Liebregts, Max; Marková, Natália; Adla, Theodor; Kara, Basak; ten Berg, Jurriën; Bonaventura, Jiří; Veselka, Josef
Abstract: Background: According to European guidelines, alcohol septal ablation (ASA) for hypertrophic obstructive cardiomyopathy (HOCM) may be less effective in patients with extensive septal scarring on cardiac magnetic resonance (CMR). This study aimed to analyze the impact of late gadolinium enhancement (LGE) on CMR on the effectiveness of ASA. Method: We conducted an observational retrospective study involving adult patients with symptomatic drug-refractory HOCM who underwent CMR before ASA at two European centres from May 2010 through June 2019. Patients were compared in binary format based on LGE presence. Moreover, a subanalysis focused on patients with septal fibrosis was performed. The effectiveness of ASA was evaluated by echocardiographic, ECG and clinical findings. Results: Of the 113 study patients, 54 (48%) had LGE on CMR. The LGE quantification performed in 29 patients revealed septal fibrosis in 17. The mean follow-up was 4.4 ± 2.6 years. Baseline parameters were similar between groups except for basal septal thickness that was greater in LGE+ group (21.1 ± 3.9 mm for LGE+ vs. 19.2 ± 3.2 mm for LGE-: p  = .005). ASA improved symptoms in all groups and reduced left ventricular outflow tract obstruction (LVOTO) (delta gradient reduction: LGE+: 62 ± 37.3%; septal LGE+: 75.6 ± 20.8%; LGE-: 72.5 ± 21.0%). However, 13% of the LGE+ and 2% of the LGE- group had residual LVOTO above 30 mmHg ( p  = .027). Conclusion: ASA was effective in all patients with HOCM, whether they had LGE on CMR or not and whether they had septal fibrosis or not. Highlights: ASA is a treatment option for patients with hypertrophic obstructive cardiomyopathy. Uncertainty over ASA efficacy in patients with myocardial fibrosis persists to date. In our study, ASA was effective in patients with HOCM independently of LGE on CMR. ASA was effective even in patients with septal fibrosis.